(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Helicobacter pylori is a spiral-shaped bacterium classified as gram-negative. Its primary mode of transmission is through oral-oral and fecal-oral routes. This bacterium induces mucosal damage and inflammation, potentially progressing from acute to chronic inflammation, ultimately increasing the risk of gastric cancer. A study involving 35 patients (14 men and 21 women) utilized the Fecal Antigen Test and Serological Test to analyze peripheral blood leukocyte count and differential. Among the findings, it was observed that the total leukocyte count and neutrophil count were significantly higher in H. pylori-positive patients (N = 24) compared to those negative for H. pylori (N = 11). Interestingly, while there was a significant difference in the total leukocyte count between H. pylori-positive and negative females, this difference was not significant in males. However, there was a notable increase in neutrophil count in both males and females with H. pylori infection, suggesting the potential utility of neutrophil count as an indicator for prognosis and diagnosis of H. pylori infection. Conversely, there was no significant correlation observed between eosinophils, lymphocytes, and other immune cells with bacterial infection, indicating minimal variation among immune cell populations in response to H. pylori infection.